The Agricultural Knowledge and Innovation System (AKIS) in Campania Region: The Challenges Facing the First Implementation of Experimental Model - Mirra, Laura; Caputo, Nicola; Gandolfi, Ferdinando; Menna, Concetta (Journal of Agricultural Policy, 2020)
Purpose: In this context, the current study aims to carry out an implementation analysis of knowledge network in Campania region, Italy. This region has implemented, using Measure 1, Measure 2 and Measure 16 of Rural Development Plan 2014-2020, an experimental model of AKIS. Methodology: The methodology was based on a living-lab approach where involved actors have an active role as co-innovators. Findings: The results give hints to implement, in the last period of the Cap 2014-2020, others experimental AKIS based on the Rural Developments Plans. Unique contribution to theory, practice and policy: The development of new agricultural practices and its spread to obtain more sustainable agriculture has become an important issue for researchers and policy makers. In particular, growing attention is paid to the Agricultural Knowledge and Innovation Systems (AKIS) expression used to describe the whole knowledge exchange system, the ways people and organisations interact within a country or a region. AKIS can include farming practice, businesses, authorities, research and can vary a lot, depending on the country or sector. However, the complexity of the AKIS implemented in Campania region requires particularly effective governance instruments and a continuous monitoring and evaluation processes to elicit innovation needs. Therefore, in the next CAP 2014-2020 measure related to advice (Art. 13 - COM (2018) 392 final) and "˜knowledge transfer and information actions' (Art. 72 - COM (2018) 392 final) should be strategically integrated to implement modern and tailored advisory programmes based on different advisory work approaches to better meet the needs of all parties. This issue needs a testing time useful to better plan policy intervention for the next CAP.